Biostratigraphic characteristics of the Chaplygin Formation Devonian of the Central and Southeastern parts of the Voronezh anteclise (Proceedings of Voronezh State University. Series: Geology, 2025)
Introduction: in the section of the sedimentary cover of the Voronezh Anteclise, the Givetian and Frasnian deposits take a great part. They are a difficult object to study from different coastal continental facies that are rarely and unevenly paleontologically characterized. Therefore, for biostratigraphic characteristics of these deposits, a variety of paleontological material (palynological, paleobotanical and paleoichthyological), was involved.Materials and Methods: the objects of the study were core material from the boreholes Novokhoperskaya 8750/1 and Shchigry-19 (Osinovka), as well as by previously obtained palynological results from boreholes located in Voronezh, Lipetsk and Belgorod regions of the Voronezh Anticlise. Standard methods were used to obtain the palynological material.Results and interpretation of the results: the results of comprehensive studies of the Devonian Chaplygin Formation of the Central and Southeastern parts of the Voronezh Anteclise are presented. Three miospore assemblages (PK2-PK4) correlated with the miospore assemblages of the Lower Frasnian Zones of Belarus. Miospore assemblages PK2-PK3 contain species typical to the Raistrickia bucera Zone from the base of the lower Frasnian (Zhelon Horizon) of Belarus, for which two phases of development are proposed: the initial, incomplete composition of R. bucera-1 miospores and a fairly complete, abundant number of R. bucera-2 species. Miospore assemblage PK4 corresponds to the Sinuosisporis vermiculatus Zone from the upper parts of the Zhelon Horizon. In the R. bucera-1 Zone, the higher plant Svalbardia aff. avelinesiana and the antiarch Asterolepis radiata were established for the first time. The Chaplygin Formation is placed in the lower half of the Lower Timan Subhorizon.Conclusion: the complex paleobotanical and macrofaunistic studies have made it possible to supplement and clarify ideas about the age of the Chaplygin Formation. For the first time, using new core materials in single continuous sections of the Yastrebov and Chaplygin Formations, we have identified sequential miospore assemblages for the central and southeastern parts of the Voronezh Anteclise from the lower, middle and upper parts of the Chaplygin Formation. These miospore assemblages are correlated with assemblages of the Lower Timan palinozones Raistrickia bucera and Sinuosisporis vermiculatus, established for the first time in Belarus at the base of the Frasnian stage, which makes it possible to attribute the Chaplygin Formation to the lower half of the Lower Timan Subhorizon. As a result of our research, we have expanded the biostratigraphic characteristics of the studied formation due to new findings of macroflora and ichthyofauna. The antiarch Asterolepis radiata and the higher plant Svalbardia aff. avelinesiana (archaeopteridae, class Progymnospermopsida) were found in the sediments of the R. bucera Zone. It was discovered in the Frasnian Chaplygin Formation (R. bucera Zone) and is the first find in Russia.
Keywords: miospores; plants; antiarchs; Givetian; Frasnian stages; Yastrebov; Chaplygin Formations